THE EFFECTIVENESS OF AROMATHERAPY AS COMPLEMENTARY THERAPY OF INSOMNIA IN STUDENTS OF FINAL SEMESTER IN POLTEKKES KEMENKES TASIKMALAYA - Nuri - Handayani (Pharmacoscript, 2019)
Insomnia is difficulty starting and maintaining sleep. People who experience insomnia have less quality and quantity of sleep so people with insomnia feel not fresh and still sleepy after woke up. The purpose of this study was to determine the description of the incidence of insomnia and the effectiveness of giving aromatherapy as one of the complementary therapies of insomnia in the final year students at the Poltekkes of the Ministry of Health Tasikmalaya.The pre-experimental with the study design Single Group Design using the Insomnia Severity Index (ISI) instrument. The purposive sampling technique used in this study and 139 respondents involved.The results of the study showed that respondents who experienced insomnia were 79.14% with various categories from mild to severe insomnia. The effectiveness of the aromatherapy shows the value of p <0.005, which means there is a significant difference between before and after giving aromatherapy to respondents.